Lifelong Learning in Validation of Prior Learning Within Vocational Mining Training in Québec (Canada) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2023)
This paper focuses on the Validation of Prior Learning (VPL) in vocational training centers, in Quebec, Canada. This training leads to the diploma of vocational studies (DVS), a level 3 diploma according to the International Standard Classification of Education (ISCED). This paper is based on research on VPL in the mining sector carried out in partnership with the Institut national des mines, an organization with the mission of supporting the education system and the mining industry in their various responsibilities pertaining to mining training. The objective of this paper is to present the VPL model in Québec vocational training and to highlight some of the challenges of continuing to implement it while keeping the focus on lifelong learning.